2013
DOI: 10.1002/jez.1817
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 3 in molluscan tissues: Localization and possible function

Abstract: The presence and localization of caspase 3, a master enzyme in apoptosis, have been analyzed in tissues of four species of Molluscs: the Bivalves Callista chione and Adamussium colbecki and the Gastropods Helix pomatia and Neobuccinum eatoni. Western blotting and immunocytochemical analyses show that a 32 kDa caspase 3 is present in guts, in gill lamellae and in digestive glands during digestion but not in heart tissue or in resting digestive glands. The enzyme is also found in gonads of both sexes but there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Apoptosis enables the adequate clearance of damaged, senescent and infected cells without inflammation [8,120,123]. Motta et al [86] analyzed the localization and possible function of the caspase-3 gene in various molluscan tissues. These authors found that caspase-3 is present in gut, gill lamellae and digestive gland during digestion but not in heart tissue or in resting digestive glands.…”
Section: Maintenance Of Tissue Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis enables the adequate clearance of damaged, senescent and infected cells without inflammation [8,120,123]. Motta et al [86] analyzed the localization and possible function of the caspase-3 gene in various molluscan tissues. These authors found that caspase-3 is present in gut, gill lamellae and digestive gland during digestion but not in heart tissue or in resting digestive glands.…”
Section: Maintenance Of Tissue Homeostasismentioning
confidence: 99%
“…The involvement of the apoptotic process in the maintenance of tissue homeostasis, physiology and functionality of each organ in mollusks is well reflected by the analysis of the expression of certain apoptotic genes in different tissues [47,86,109]. In the mussel (M. galloprovincialis) [109], the apoptotic process in the different anatomical parts of the digestive gland appears to be quite important because it is the first entrance for potential pathogens such as the copepod Mytilicola intestinalis [31,133].…”
Section: Maintenance Of Tissue Homeostasismentioning
confidence: 99%
“…However, other mechanisms can lead to DNA fragmentation that would result in a positive TUNEL labelling, and for this reason the TUNEL methodology has been criticized [48][49][50]. It is nevertheless a standard procedure that has already been applied in mollusk tissues, and in association with active caspase-3 immunolocalization to detect apoptosis in the chemosymbiotic bivalve Codakia orbiculata [40,51]. Caspase-3 exists within the cytosol as inactive dimers.…”
Section: Relevance Of Tunel Labelling To the Study Of Apoptosis In Dementioning
confidence: 99%
“…Apoptosis is an intrinsic, genetically controlled process, responsible for destroying redundant, dysfunctional or damaged cells (Motta et al 2013). Among the genes that were more abundant in poor quality oocytes, some appeared to be implicated in cell responses to stress.…”
Section: Stress and Apoptosismentioning
confidence: 99%